1994
DOI: 10.1128/jcm.32.9.2192-2196.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immunoaffinity purification of baculovirus-expressed rubella virus E1 for diagnostic purposes

Abstract: Three monoclonal antibodies, termed 4E10, lE11:10, and 2D9:1, were generated against rubella virus. lmmunoblot analysis with purified authentic rubella virus or recombinant baculovirus-expressed rubella virus structural proteins El, E2, and C demonstrated that they were directed against the El envelope glycoprotein of the rubella virus particle. By using the yeast Ty virus-like particle system, it was possible to map the binding site of lE11:10 within amino acids 236 to 286 of the El protein and the binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The discrepancy between the reported theoretical molecular weight of 37 kDa and the observed migration in SDS‐PAGE gels corresponding to a 50 kDa size is most likely due to glycosylation. This has been reported for a number of proteins, including mTSLPR (10–12, 26–28). In addition, both a commercial anti‐mTSLPR antiserum as well as a monoclonal anti‐histidine antibody stained identical 50 kDa bands, whereas none of the tested antibodies could identify a corresponding band in the control cell lysate prepared from recombinant FastBacHisC baculovirus‐infected insect cells (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…The discrepancy between the reported theoretical molecular weight of 37 kDa and the observed migration in SDS‐PAGE gels corresponding to a 50 kDa size is most likely due to glycosylation. This has been reported for a number of proteins, including mTSLPR (10–12, 26–28). In addition, both a commercial anti‐mTSLPR antiserum as well as a monoclonal anti‐histidine antibody stained identical 50 kDa bands, whereas none of the tested antibodies could identify a corresponding band in the control cell lysate prepared from recombinant FastBacHisC baculovirus‐infected insect cells (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…It has previously been shown that the baculovirus expression vector system is capable of producing significant amounts of RV-specific proteins (21,23,29) and that recombinant proteins have potential in screening for RV-specific antibodies (12,28). In addition, procaryotic and other eucaryotic systems, as well as synthetic peptide technology, have been used to produce RV-specific antigens in hopes of replacing the expensive and infectious authentic RV antigen (1,9,19,31,34).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of recombinant E1. The supernatant fraction was applied to an immunoaffinity column with the monoclonal antibody, 4E10, coupled to a CNBractivated Sepharose 4B gel (Pharmacia, Uppsala, Sweden), as recently described (12). The cytoplasmic extract containing recombinant RV-E1 protein was mixed (end over end) with the affinity matrix at 4ЊC overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the rubella virus antigen, most assays were based upon whole-virus extracts. But recently, EIAs using synthetic rubella virus proteins (8,12) and recombinant E1 proteins (6) have been developed.…”
mentioning
confidence: 99%